The genesis of the idea of freedom of religious conscience in the Middle Ages - Babii, Mykhailo (Relihijna svoboda, 2020)
The article is devoted to the idea of freedom of conscience, the processes of developing its understanding in the Middle Ages, the opposition of various approaches, which are represented by thinkers of the Western and Eastern Christian tradition. These traditions were formed and developed within the framework of interpretive assessments of the relationship between the state and the church, known as Caesaropapism and Papоcaesarism. The peculiarities of Western Christian and Eastern Christian approaches to issues of freedom of conscience, which were formed by the nature of state power and its relations with the church, are analyzed. The Catholic understanding of relations was based on the independence of the church from the state, on its freedom, on the opposition of the spiritual and the earthly, on the supremacy of the former over the latter. It is claimed that the Roman Catholic Church has always claimed complete control over the secular state. According to the Orthodox view, the "spiritual and secular" should be integrated into one "symphonic" system with the leading role of the state. The church "gave its freedom" to the Caesars. The mechanism of the emergence of religious alternatives to the official teachings of the church, in particular heresies, sectarianism, schism, which served as a breeding ground for the emergence of religious freedom, freedom in the church. The role of the rationalist and anti-church component, philosophical and theological concepts, which were determined by a significant increase in scientific knowledge and the development of philosophical teachings, which also led to ideas of freedom of conscience, is emphasized. During this period, the genesis of the idea of freedom of conscience was played by the substantiation of the idea of human rights, in particular, the right to freedom of conscience and religion. The Middle Ages are presented as a specific era, which is associated with previous periods in the intellectual - philosophical and theological - understanding of freedom of conscience, in which despite all the negative socio-political, religious processes, persecution of freethinkers, formed principles of freedom of conscience and theoretical justification future paradigm. During this period, it was mainly about freedom of religious conscience, about the freedom of the church, about conscience, freedom of will, and not about freedom of conscience. It was important to substantiate the idea of the right of the autonomous mind, the doctrine of "natural light", the distinction between the concepts of "sacred" and "secular". At the same time, freedom of religious conscience can be said only for Christian believers, all others - infidels, "schismatics", heretics - were outlawed, society considered them as enemies of the state and the church. Heretical movements, which originated in the bosom of the Christian church and were determined by the context and events of the Middle Ages, became the environment where the ideas of freedom of conscience, including freedom of religious conscience, religious tolerance received "energy" for their development and manifestation as a public demand.